Ineradicable System Vulnerabilities in the Anesthesia Pre-Filled Syringe Medication Management Process. (September 2014) - Yang, Yushi; Joy Rivera, A.; Fortier, Christopher; Abernathy, James
Pre-filled medication syringes (PFS) are injection devices that were recently introduced into the anesthesia medication management process to enhance safety, affordability, and convenience. However, it is still uncertain how well PFS integrate within the process and whether they effectively eliminate the system vulnerabilities (SV) associated with the traditional self-filled medication syringe (SFS) process. Two Human Factors Engineers conducted observations of 17 general surgery cases with either SFS or PFS. Aggregating the observation data, four ineradicable SV in the process with PFS were identified. Participants rated these ineradicable SV based on their occurrence, their severity to patients, and the disruptiveness to the operating room (OR) workflow. Results show that while PFS resolve SV to some degree, they are not panacea to all the problems in the anesthesia medication management process. Organizational-level interventions are needed for the elimination of all SV.